Eliminating insoluble products and enhancing reversible CO2 capture of a tetraethylenepentamine-based non-aqueous absorbent: Exploring the synergistic regulation of 2-amino-2-methyl-1-propanol and n-propanol - Xiaobin Zhou; Yunqiong Tang; Chao Liu; Shengpeng Mo; Yinming Fan; Dunqiu Wang; Bihong Lv; Yanan Zhang; Yinian Zhu; Zongqiang Zhu; Guohua Jing (Carbon Capture Science & Technology)
To tackle the prevalent challenges encountered with polyamine-based non-aqueous absorbents (NAAs), particularly the formation of viscous products and inferior regeneration performance, this study proposed an innovative synergistic regulation strategy that integrated 2-amino-2-methyl-1-propanol (AMP) and n-propanol (NPA). Accordingly, a novel tertiary tetraethylenepentamine (TEPA)-AMP-NPA (T-A-N) NAA was devised. The optimized T-A-N maintained complete homogeneity throughout the entire CO2 absorption process and achieved an impressive CO2 loading of 1.15 mol·mol−1 while maintaining a low viscosity of merely 22.47 mPa·s. Remarkably, its absorption capacity showed little decrement after four consecutive absorption-desorption cycles, underscoring its exceptional recyclability. Within the T-A-N system, AMP underwent a reaction with CO2, yielding AMP-carbamate and protonated AMP, while TEPA engaged in CO2 absorption to form zwitterionic carbamates. During the desorption process, NPA served as a regeneration activator, facilitating the conversion of stable TEPA-carbamates into less stable alkyl carbonate intermediates, thereby enhancing the T-A-N's regeneration performance. Moreover, the T-A-N system addressed the issue of TEPA-carbamate self-aggregation into insoluble gelatinous substances by leveraging the synergistic enhancement effects between AMP derivatives and NPA. Specifically, these components effectively bound TEPA-carbamate species via robust electrostatic affinity and intermolecular hydrogen-bond interactions, inhibiting their self-aggregation and preventing the formation of insoluble products. Furthermore, T-A-N exhibited a significant reduction in both sensible and latent heat requirements, by 67 % and 82 % respectively, compared to 30 wt% MEA, highlighting its advantageous energy-saving potential for CO2 capture. Overall, harnessing the synergistic enhancement effects of AMP and NPA was conducive to the development of polyamine-based NAAs that offered superior CO2 capture reversibility, low energy consumption, and resistance to insoluble product formation.